From Natural to Artificial Antitumor Lipidic Alkynylcarbinols: Asymmetric Synthesis, Enzymatic Resolution, and Refined SARs - Listunov, Dymytrii; Joly, Etienne; Rullière, Pauline; Gaspard, Hafida; Bernardes-Génisson, Vania; Génisson, Yves; Maraval, Valérie; Chauvin, Remi (Synthesis, 2018)
Among acetylenic natural products, chiral lipidic alkynylcarbinol (LAC) metabolites, mostly extracted from marine sponges, have revealed a broad spectrum of biological activities, in particular, remarkable antitumor cytotoxicity. With reference to one of the simplest natural representatives, [(S)-eicos-(4E)-en-1-yn-3-ol], and a given cancer cell line (HCT116), combined extensive efforts in chemical synthesis (relying on the use of a large chemical toolbox) and biological analysis (in vitro tests), have provided systematic structure–activity relationships (SARs) where the initially selected four structural parameters appear as independent principal components: (i) and (ii) the sp/sp2 content and extent of the terminal and internal unsaturations adjacent to the carbinol center, (iii) the absolute configuration of the latter, (iv) the length of the n-aliphatic backbone. Two key criteria have also been established regarding the functional alkynylcarbinol pharmacophore: the alkynylcarbinol unit must be both secondary and terminal (i.e., substituted by a short ethynyl or ethenyl C2 group). This review is intended to provide a further illustration of the value of a simple rational approach for drug design, and to act as a benchmark for future optimization of LACs as antitumor agents.1 Introduction2 2C2-Unsaturated Pharmacophore Candidates2.1 Alkenylalkynylcarbinols (AACs)2.2 Dialkynylcarbinols (DACs or DACys)2.3 Alkynylalkenylcarbinols (iso-AACs) and Dialkenylcarbinols (DACes)2.4 Oxidation-Protected Dialkynylcarbinols and Dialkynylketones2.5 Fluorophore-Labeled Lipidic Dialkynylcarbinols3 C2/C3-Unsaturated Pharmacophore Candidates3.1 Cyclopropylalkynylcarbinols (CACs)3.2 Allenylalkynylcarbinols (AllACs)4 C2/C4- and 3C2-Unsaturated Pharmacophore Candidates4.1 Butadiynylalkynylcarbinols (BACs)4.2 Trialkynylcarbinols (TACs)5 Double-AC-Headed Pharmacophore Candidates6 Screening on the Lipidic Chain Length7 Conclusion
Keywords: alkynes; asymmetric synthesis; antitumor cytotoxicity; chiral propargylic alcohols; lipidic alkynylcarbinols; marine drugs; stereoselectivity; structure–activity relationships